1987
DOI: 10.1002/jat.2550070211
|View full text |Cite
|
Sign up to set email alerts
|

A 13‐week vapor inhalation study of 3,3‐dimethyl‐2‐butanol in sprague‐dawley rats

Abstract: Four groups of male and female Sprague-Dawley rats were exposed for 13 weeks to 3,3-dimethyl-2-butanol (PA) at concentrations of 0.00, 0.20, 1.00 or 5.00 mg/l (1 mg/l = 240 ppm). Exposures were for 6 hr per day, 5 days per week with sacrifices at 7 and 13 weeks of exposure, and at 4 weeks after exposure. The test animals were evaluated for abnormalities in physiology, behaviour, clinical laboratory parameters, and gross and microscopic morphology. No abnormalities were detected in electrocardiograms, respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Inhalation studies with rats have shown ataxia, mild hypoxemia, hypercapnia, and lacrimation (James et al 1987b). LCLo in rat was 4930 mg/kg for a 6 hours exposure period per day for 13 week inhalation study (James et al 1987a). The rats also showed depressed respiration and reduced motor activity upon an exposure.…”
Section: -Hexanolmentioning
confidence: 99%
“…Inhalation studies with rats have shown ataxia, mild hypoxemia, hypercapnia, and lacrimation (James et al 1987b). LCLo in rat was 4930 mg/kg for a 6 hours exposure period per day for 13 week inhalation study (James et al 1987a). The rats also showed depressed respiration and reduced motor activity upon an exposure.…”
Section: -Hexanolmentioning
confidence: 99%
“…The concentration range of pinacolyl alcohol investigated should be lower than 5 mg L −1 , which was compatible with the requirements of the industry or other stakeholders [19,20]. The aim of this paper is to develop a highly selective pina- colyl alcohol sensor based on CTL for the determination of pinacolyl alcohol in workplace air.…”
Section: Introductionmentioning
confidence: 81%
“…A rapidly growing number of chemicals -principally aliphatic or aromatic hydrocarbons -have been reported to induce a characteristic spectrum of morphological changes in the kidney unique to the male rat (Carpenter et al 1975a(Carpenter et al , b, 1977Parker et al 1981;Alden et al 1984;Phillips and Cockrell 1984;Phillips and Egan 1984;Collins and Manus 1987;James et al 1987;Kanerva et al 1987a;Phillips et al 1987;Bomhard et al 1988Bomhard et al , 1989.…”
Section: Introductionmentioning
confidence: 99%